Importance of Clinical Worsening of Heart Failure Treated in the Outpatient Setting: Evidence From the Prospective Comparison of ARNI With ACEI to Determine Impact on Global Mortality and Morbidity in Heart Failure Trial (PARADIGM-HF). Issue 23 (7th June 2016) - Okumura, Naoki; Jhund, Pardeep S.; Gong, Jianjian; Lefkowitz, Martin P.; Rizkala, Adel R.; Rouleau, Jean L.; Shi, Victor C.; Swedberg, Karl; Zile, Michael R.; Solomon, Scott D.; Packer, Milton; McMurray, John J.V.
Abstract : Background—: Many episodes of worsening of heart failure (HF) are treated by increasing oral therapy or temporary intravenous treatment in the community or emergency department (ED), without hospital admission. We studied the frequency and prognostic importance of these episodes of worsening in the Prospective Comparison of ARNI (angiotensin-receptor-neprilysin inhibitor) with ACEI (angiotensin-converting enzyme inhibitor) to Determine Impact on Global Mortality and Morbidity in Heart Failure Trial (PARADIGM-HF). Methods and Results—: Outpatient intensification of HF therapy was added to an expanded composite outcome with ED visits, HF hospitalizations, and cardiovascular deaths. In an examination of first nonfatal events, 361 of 8399 patients (4.3%) had outpatient intensification of HF therapy without a subsequent event (ie, ED visit/HF hospitalizations) within 30 days; 78 of 8399 (1.0%) had an ED visit without previous outpatient intensification of HF therapy or a subsequent event within 30 days; and 1107 of 8399 (13.2%) had HF hospitalizations without a preceding event. The risk of death (in comparison with no-event patients) was similar after each manifestation of worsening: outpatient intensification of HF therapy (hazard ratio, 4.8; 95% confidence interval, 3.9–5.9); ED visit (hazard ratio, 4.5; 95% confidence interval, 3.0–6.7); HF hospitalizations (hazard ratio, 5.9; 95% confidence interval, 5.2–6.6). The expanded composite added 14% more events and shortened time to accrual of a fixed number of events. The benefit of sacubitril/valsartan over enalapril was similar to the primary outcome for the expanded composite (hazard ratio, 0.79; 95% confidence interval, 0.73–0.86) and was consistent across the components of the latter. Conclusions—: Focusing only on HF hospitalizations underestimates the frequency of worsening and the serious implications of all manifestations of worsening. For clinical trials conducted in an era of heightened efforts to avoid HF hospitalizations, inclusion of episodes of outpatient treatment intensification (and ED visits) in a composite outcome adds an important number of events and shortens the time taken to accrue a target number of end points in an event-driven trial. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT01035255. Abstract : Supplemental Digital Content is available in the text.